2017
DOI: 10.1111/tri.12981
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the recovery of injured porcine lungs with prolonged normothermic cellularex vivolung perfusion following donation after circulatory death

Abstract: Donation after circulatory death (DCD) is an underused source of donor lungs. Normothermic cellular ex vivo lung perfusion (EVLP) is effective in preserving standard donor lungs but may also be useful in the preservation and assessment of DCD lungs. Using a model of DCD and prolonged EVLP, the effects of donor warm ischemia and postmortem ventilation on graft recovery were evaluated. Adult male swine underwent general anesthesia and heparinization. In the control group (n = 4), cardioplegic arrest was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…Before EVLP, the only testing platform for extended‐criteria donor lungs was the recipient. EVLP now allows evaluation, preservation, and reconditioning of these organs prior to transplant . We have previously demonstrated that the hemodynamics and compliance of swine DCD lungs normalize relative to standard donors during 24H normothermic EVLP, although more injured lungs had worse oxygenation .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Before EVLP, the only testing platform for extended‐criteria donor lungs was the recipient. EVLP now allows evaluation, preservation, and reconditioning of these organs prior to transplant . We have previously demonstrated that the hemodynamics and compliance of swine DCD lungs normalize relative to standard donors during 24H normothermic EVLP, although more injured lungs had worse oxygenation .…”
Section: Discussionmentioning
confidence: 98%
“…Notably absent from our study are donors subjected to unventilated warm ischemia. This decision was made based on our previous data demonstrating superior EVLP performance of donor lungs preserved following ventilated warm ischemia . We do not believe that the procurement, preservation, and transplant of lungs from a donor that experiences prolonged warm unventilated ischemia comports to any realistic clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] Our group has reported experience with prolonged (~24 hours) preservation of porcine donor lungs from beating-heart and DCD donors in an acceptable functional state with the use of a portable normothermic EVLP system (Organ Care System [OCS] Lung [TransMedics]), combined with a perfusate based on autologous donor whole blood (ADWB) and a low-potassium dextran crystalloid solution (OCS Lung solution [TransMedics]). [19][20][21][22] While the most commonly considered measurement of allograft function when considering lung donors and during EVLP is the PaO 2 :FiO 2 (P:F) ratio, we have demonstrated the value of other measurements when evaluating the function of allografts from beating-heart and DCD donors during prolonged preservation, including pulmonary vascular resistance (PVR) and allograft edema formation. 19,21 In the current study, we replicated our model of prolonged preservation in a cohort of human donor lungs.…”
mentioning
confidence: 99%
“…[19][20][21][22] While the most commonly considered measurement of allograft function when considering lung donors and during EVLP is the PaO 2 :FiO 2 (P:F) ratio, we have demonstrated the value of other measurements when evaluating the function of allografts from beating-heart and DCD donors during prolonged preservation, including pulmonary vascular resistance (PVR) and allograft edema formation. 19,21 In the current study, we replicated our model of prolonged preservation in a cohort of human donor lungs. We sought to identify and procure bilateral lung blocks from human donors that had been…”
mentioning
confidence: 99%